Diagnosing phosphorus limitations in natural terrestrial ecosystems in carbon cycle models. Issue 7 (18th July 2017) - Sun, Yan; Peng, Shushi; Goll, Daniel S.; Ciais, Philippe; Guenet, Bertrand; Guimberteau, Matthieu; Hinsinger, Philippe; Janssens, Ivan A.; Peñuelas, Josep; Piao, Shilong; Poulter, Benjamin; Violette, Aurélie; et al.
Abstract: Most of the Earth System Models (ESMs) project increases in net primary productivity (NPP) and terrestrial carbon (C) storage during the 21st century. Despite empirical evidence that limited availability of phosphorus (P) may limit the response of NPP to increasing atmospheric CO2, none of the ESMs used in the previous Intergovernmental Panel on Climate Change assessment accounted for P limitation. We diagnosed from ESM simulations the amount of P need to support increases in carbon uptake by natural ecosystems using two approaches: the demand derived from (1) changes in C stocks and (2) changes in NPP. The C stock‐based additional P demand was estimated to range between −31 and 193 Tg P and between −89 and 262 Tg P for Representative Concentration Pathway (RCP) 2.6 and RCP8.5, respectively, with negative values indicating a P surplus. The NPP‐based demand, which takes ecosystem P recycling into account, results in a significantly higher P demand of 648–1606 Tg P for RCP2.6 and 924–2110 Tg P for RCP8.5. We found that the P demand is sensitive to the turnover of P in decomposing plant material, explaining the large differences between the NPP‐based demand and C stock‐based demand. The discrepancy between diagnosed P demand and actual P availability (potential P deficit) depends mainly on the assumptions about availability of the different soil P forms. Overall, future P limitation strongly depends on both soil P availability and P recycling on ecosystem scale. Key Points: None of the ESMs used in the IPCC AR5 accounted for the effect of P limitation on the increase in NPP and carbon storage Future additional P demand was estimated to have very large uncertainties under different climate scenarios and approaches Future P limitation strongly depends on soil P availability, litter P turnover, the C:P stoichiometry of plant, and the P content in soil organic matter Plain Language Summary: Phosphorus (P) is a fundamental component of all living organisms. Low available P in soils is considered to be a limiting factor for plant growth in a majority of ecosystems. Increases in projected productivity and carbon (C) sinks in the next few decades need higher P input and/or enhanced P recycling to support. If soil available P and P input into natural ecosystems cannot keep pace with the increased demand of P by increased future carbon sink in natural ecosystems, then the future carbon sink could be reduced. The magnitude of land carbon sink on mitigating climate change also depends on future P limitation. In this study, we diagnosed future additional P demand of natural ecosystems by two approaches, and these two approaches get very different magnitude of P limitation on future carbon sink. The large uncertainty between the two approaches is caused by processes of P cycle such as litter P turnover and parameters such as soil and plant stoichiometry. In addition, large uncertainty of soil available P also leads to large uncertainty in future P limitation. To reduce the large uncertainty of future P limitation, soil available P and key processes of P cycle needs further investigation.